2016
DOI: 10.1007/s00033-015-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of finite deformable, biphasic biological tissues with transversely isotropic statistically distributed fibers: toward a practical solution

Abstract: The distribution of collagen fibers across articular cartilage layers is statistical in nature. Based on the concepts proposed in previous models, we developed a methodology to include the statistically distributed fibers across the cartilage thickness in the commercial FE software COMSOL which avoids extensive routine programming. The model includes many properties that are observed in real cartilage: finite hyperelastic deformation, depth-dependent collagen fiber concentration, depth- and deformation-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The cervical discs are complex in mechanical properties; they are not only biphasic, composed of a solid and a fluid phase, but also anisotropic due to the reinforce effects of the distributed collagen fibers within the tissues. 39 If the major concern is the injury mechanism of the cervical discs, it is necessary to know the loading share between the fluid and solid phases; in that case, the interstitial fluid and collagen become non-negligible effects. However, in this study, we need to only know the mechanical response of the cervical discs when subjected to shock load; we are not interested in the detailed stress/strain distributions within the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical discs are complex in mechanical properties; they are not only biphasic, composed of a solid and a fluid phase, but also anisotropic due to the reinforce effects of the distributed collagen fibers within the tissues. 39 If the major concern is the injury mechanism of the cervical discs, it is necessary to know the loading share between the fluid and solid phases; in that case, the interstitial fluid and collagen become non-negligible effects. However, in this study, we need to only know the mechanical response of the cervical discs when subjected to shock load; we are not interested in the detailed stress/strain distributions within the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Their results concluded that the fibers realigned themselves differently in each zone of the construct to resist the applied load. Anisotropic representation of the fibers is more realistic as the fiber distribution in articular cartilage changes between zones [36]. Therefore, any FEA of scaffold design should include orientation and depth-dependent fiber distribution.…”
Section: Components Of Finite Element Analysismentioning
confidence: 99%
“…These models leverage enhanced understanding of the local mechanical environment in cartilage tissue under injurious loading and around structural defects as well as its contribution to cartilage damage. To this end, several in silico models were introduced in the literature ( Keenan et al, 2013 ; Wu et al, 2016 ; Koh et al, 2019 ; Wang et al, 2019 ). Among the proposed models, a fibril-reinforced poro-viscoelastic swelling (FRPVES) finite element (FE) model introduced by Wilson et al (2005) accounts for different ECM constituents (i.e., collagen content, fibril orientation, PG content, and water content) and therefore allows studying the effect of variations in cartilage composition due to the altered mechanical environment.…”
Section: Introductionmentioning
confidence: 99%